Lessons learned from volar plate fixation of scaphoid fracture nonunions. (January 2018) - Dodds, Seth D.; Williams, John B.; Seiter, Max; Chen, Clark
Treating scaphoid nonunions presents difficulties particularly when there is bone loss, significant humpback deformity or avascular necrosis. We describe a new type of fixation with a volar scaphoid plate that adds to the methods of internal fixation that are available for the treatment of recalcitrant scaphoid nonunions. We will also discuss 'lessons learned' from a cases series. The case series includes 20 consecutive patients treated with volar buttress plating and a pedicled vascularized bone graft from the ipsilateral volar distal radius. There was clinical and radiographic evidence of union in 18 of 20 patients, 13 of which were verified by computed tomographic scan. The range of motion was improved in all patients post-operatively. Four patients with radiographic union experienced intermittent clicking with maximal wrist flexion, believed to be due to the impingement of the plate on the volar aspect of the radioscaphoid articulation and underwent removal at approximately 1 year after the index procedure. Volar scaphoid plating is a useful alternative to headless scaphoid screw fixation in the treatment of unstable scaphoid waist fractures and nonunions. Level of evidence: IV